Respuesta :

Answer:

Option B and C are correct.

Step-by-step explanation:

Inverse function: If both the domain and the range are R for a function f(x), and if f(x) has an inverse g(x) then:

[tex]f(g(x)) = g(f(x)) = x[/tex] for every x∈R.

Let [tex]f(x) = \frac{1}{2}(\ln(\frac{x}{2}) -1)[/tex] and [tex]g(x) = 2e^{2x+1}[/tex]

Use logarithmic rules:

  • [tex]ln e^a = a[/tex]
  • [tex]e^{lnx} = x[/tex]
  • [tex]\ln a^b = b\ln a[/tex]

then, by definition;

[tex]f(g(x)) = f(2e^{2x+1}) =\frac{1}{2}(\ln(\frac{2e^{2x+1}}{2})-1)[/tex] = [tex]\frac{1}{2}(\ln(e^{2x+1}}){-1) = \frac{1}{2} (2x+1-1) =\frac{1}{2}(2x) = x[/tex]

[tex]g(f(x)) = g(\frac{1}{2}(\ln(\frac{x}{2}) -1)) = 2e^{2({\frac{1}{2}(\ln(\frac{x}{2}) -1})+1[/tex] [tex]2e^{(\ln(\frac{x}{2}) -1+1}=2e^{\ln(\frac{x}{2})} =2\cdot \frac{x}{2} = x[/tex]

Similarly;

for [tex]f(x) = \frac{4 \ln(x^2)}{e^2}[/tex] and [tex]g(x) = e^{\frac{e^2 \cdot x}{8} }[/tex]

then, by definition;

[tex]f(g(x)) = f(e^{\frac{e^2 \cdot x}{8}}) =\frac{4 \ln {(\frac{e^2 \cdot x}{8})^2}}{e^2}[/tex] = [tex]\frac{8 \ln {(\frac{e^2 \cdot x}{8})}}{e^2} =\frac{8\frac{e^2\cdot x}{8} }{e^2}=\frac{8e^2 \cdot x}{8e^2}=x[/tex]

Similarly,

g(f(x)) = x

Therefore, the only option B and C are correct. As the pairs of functions are inverse function.

ACCESS MORE